A 13-week subchronic toxicity study of heme iron in SD rats. (May 2023) - Matsushita, Kohei; Toyoda, Takeshi; Akane, Hirotoshi; Morikawa, Tomomi; Ogawa, Kumiko
Abstract: Heme iron (HI ) has been widely used as a food additive and supplement to support iron fortification. However, no sufficient toxicological data to evaluate the safety of HI have been reported. In the current study, we performed a 13-week subchronic toxicity study of HI in male and female Crl:CD(SD) rats. Rats were orally administered HI in the diet at concentrations of 0%, 0.8%, 2%, and 5%. Observations of general condition, body weight (bw) and food consumption, urinalysis, hematology, serum biochemistry, and macroscopic and histopathological examination were performed. The results showed that HI had no adverse effects on any of the examined parameters. Therefore, we concluded that the no-observed-adverse-effect level (NOAEL) for HI was estimated to be 5% for both sexes (2, 890 mg/kg bw/day for males and 3, 840 mg/kg bw/day for females). Since the iron content of HI used in this study was in a range of 2.0–2.6%, iron content at NOAEL for HI was calculated to be 57.8–75.1 mg/kg bw/day for males and 76.8–99.8 mg/kg bw/day for females. Highlights: Heme iron (HI) was assessed for 13-week subchronic toxicity. There were no toxicological effects by HI treatment. The NOAEL for HI was estimated to be 2, 890 and 3, 840 mg/kg bw/day for males and females, respectively.